2006
DOI: 10.1144/gsl.sp.2006.255.01.01
|View full text |Cite
|
Sign up to set email alerts
|

Cool-water carbonate ramps: a review

Abstract: This review of marine, cool-water carbonate ramps considers both their defining features and the key publications relating to them. Cool-water carbonate environments are dominated by open, skeletal debris-covered sea bottoms which support biological assemblages devoid of hermatypic coral reefs, calcified green algae and non-skeletal grains. The growing body of modem literature deals mainly with Neogene to Recent examples, particularly from the Australian, New Zealand and Mediterranean regions. Nevertheless, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…The temporal transition from photozoan to heterozoan mode of life of the benthic community as an effect from palaeoenvironmental changes during the early Valanginain (see 6.3.2.) may have led to development of a non-rimmed (ramp-like) platform profile (James, 1997;Pomar, 2001;Pomar et al, 2004;Pedley and Carannante, 2006;F€ ollmi et al, 2007;Brigaud et al, 2014). Possible evidence comes from those redeposited gravel-sized clasts of the Aliki Limestones that are interpreted as products of shoal, back-shoal and fore-shoal environments on the platform interior (Fig.…”
Section: Evidence For Emersion and Major Hiatusmentioning
confidence: 99%
“…The temporal transition from photozoan to heterozoan mode of life of the benthic community as an effect from palaeoenvironmental changes during the early Valanginain (see 6.3.2.) may have led to development of a non-rimmed (ramp-like) platform profile (James, 1997;Pomar, 2001;Pomar et al, 2004;Pedley and Carannante, 2006;F€ ollmi et al, 2007;Brigaud et al, 2014). Possible evidence comes from those redeposited gravel-sized clasts of the Aliki Limestones that are interpreted as products of shoal, back-shoal and fore-shoal environments on the platform interior (Fig.…”
Section: Evidence For Emersion and Major Hiatusmentioning
confidence: 99%
“…As we see by the correlation, the widely changing thicknesses of sedimentary units and sedimentary features, traces of volcanic activities, or abrupt facies changes in the studies areas have not been observed, which implies that the change in the Middle Eocene rate of sea-level have been the primary control on facies, depositional environments and stratigraphic architecture (Pedley andCarannante, 2006, Nalin andMassari, 2009). Such inference is also supported by the plausible match of our detailed correlations with the global sea level curves of Haq (1988) and Snedden and Chengjie (2010) (Fig.…”
Section: Thickness Distribution Description Interpretationmentioning
confidence: 83%
“…Our study focuses on interpreting the genesis and features of the rhythmic succession. Although cool-water carbonate deposition is often controlled by relatively short-term eustatic changes (Hansen 1999;Tesson et al 2000), following Pedley and Carannante (2006) we propose as an alternative that the ramp rhythmicity can be controlled by short-period catastrophic changes in climate. Whereas eustasy is the main regulator, climate and oceanography determine terrigenous clastic sediment supply and carbonate productivity and thus the character of the sedimentary deposits (Lukasik and James 2006).…”
Section: Introductionmentioning
confidence: 89%
“…Instead, the predominant sedimentary structures here are tabular crossstratification, representing unidirectionally migrating bedforms. The Mediterranean region has remained microtidal at least since the early Miocene, when its connection to the Indian Ocean was lost (Pedley and Carannante 2006). Waves generate both longshore currents and landward tractive flows (Stokes drift).…”
Section: Sediment Dispersalmentioning
confidence: 99%